Transformational Leadership, Work Motivation, And Emotional Intelligence To Contract Employee Satisfaction - I Wayan Adnyana Wijaya; I Gede Riana (Ridwan Institute, 2022)
Quality employee management can contribute to job happiness because employees believe their expectations have been met, but it can also lead to job discontent if those expectations are not satisfied. The goal of this research was to see how transformational leadership, work motivation, and emotional intelligence affected employee job satisfaction. The participants in this study were contract staff from the Faculty of Medicine at Udayana University in Bali, numbering up to 70. The number of samples is determined using the census sampling technique. This study's primary data came from the distribution of questionnaires to respondents who met the set criteria; the study's secondary data came from other sources. The findings revealed that transformational leadership, work drive, and emotional intelligence all had a partial or simultaneous effect on employee job satisfaction. The study's findings suggest that transformational leadership, work drive, and emotional intelligence all have a role in enhancing contract employees' job happiness, which leads to increased productivity